2018
DOI: 10.1037/bne0000230
|View full text |Cite
|
Sign up to set email alerts
|

Spared motivational modulation of cognitive effort in a maternal immune activation model of schizophrenia risk.

Abstract: Maternal immune activation (MIA) during gestation is a significant risk factor for development of schizophrenia and other neurodevelopmental diseases. In animal models of this risk factor, MIA during pregnancy can produce offspring that recapitulate certain aspects of the behavioral and neurophysiological impairments seen in schizophrenia. Here, the authors tested the effect of polyinosinic-polycytidylic acid (poly I:C)-induced MIA in a task that explicitly assays the interaction between motivation and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(87 reference statements)
1
9
0
Order By: Relevance
“…20-30°C), the more robust (i.e., longer-lasting) effect of high-dose Poly IC is hypothermia [68]. Similar to behavioral symptoms seen in individuals with schizophrenia and ASD, offspring that were prenatally treated with Poly IC have been reported to have significant abnormalities in several behaviors, including deficits in the pre-pulse inhibition [62,63,[69][70][71], acoustic startle response, decreases in exploratory behavior in both open-field and novel-object tests, increased immobility in the forced swim test, and decreases in social interactions and sucrose/saccharine preferences [64,[72][73][74][75][76][77][78][79][80][81][82]. Importantly, many of these effects are dependent on the prenatal timing, Poly IC dosing, and genetic background of animals.…”
Section: Immune Activationmentioning
confidence: 99%
“…20-30°C), the more robust (i.e., longer-lasting) effect of high-dose Poly IC is hypothermia [68]. Similar to behavioral symptoms seen in individuals with schizophrenia and ASD, offspring that were prenatally treated with Poly IC have been reported to have significant abnormalities in several behaviors, including deficits in the pre-pulse inhibition [62,63,[69][70][71], acoustic startle response, decreases in exploratory behavior in both open-field and novel-object tests, increased immobility in the forced swim test, and decreases in social interactions and sucrose/saccharine preferences [64,[72][73][74][75][76][77][78][79][80][81][82]. Importantly, many of these effects are dependent on the prenatal timing, Poly IC dosing, and genetic background of animals.…”
Section: Immune Activationmentioning
confidence: 99%
“…However, it is becoming increasingly clear that such models are variable, subject to PIC batch effects (Careaga et al, 2018;Kowash et al, 2019;Mueller et al, 2019), and at least in some laboratories do not adequately model the full range of cognitive or motivational impairments seen in patients (Bates et al, 2018;Gray et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that combining separate neurodevelopmental interventions, like MIA and isolation rearing, into a dual-hit model might overcome some of their individual limitations (Bates et al, 2018;Shortall et al, 2018). Crucially it appears that even subclinical MIA can increase vulnerability of the offspring to a second hit, thus increasing the likelihood of environmental stressors causing a schizophrenia-or ASD-like phenotype (Estes and McAllister, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To study the interaction between motivation and attention, we developed the Signaled Probability Sustained Attention (SPSA; Figure 1 ) task ( Ward et al, 2015a , b ; Hall-McMaster et al, 2017 ; Bates et al, 2018 ). In this prefrontal-dependent sustained-attention task ( Kahn et al, 2012 ) rats must attend to cues that signal which of two responses will be rewarded on each trial.…”
Section: Introductionmentioning
confidence: 99%